2020
DOI: 10.1186/s12877-020-01659-9
|View full text |Cite
|
Sign up to set email alerts
|

“Establishing the criterion validity of the interRAI Check-Up Self-Report instrument”

Abstract: Background: Low and middle-income countries have growing older populations and could benefit from the use of multi-domain geriatric assessments in overcoming the challenge of providing quality health services to older persons. This paper reports on the outcomes of a study carried out in Cape Town, South Africa on the validity of the interRAI CheckUp Self-Report instrument, a multi-domain assessment instrument designed to screen older persons in primary health settings. This is the first criterion validity stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…Leveraging physician determination as a criterion is an appropriate measure to test experimental validity in this circumstance, as there is no gold-standard classification to establish appropriateness or has not been experimentally validated. 28 Given validation testing tends to perform better on data used to construct a classification or scale, examining EDAC with a panel of physicians who are unaware of the EDAC’s components can provide a more unbiased estimate of EDAC’s true accuracy and performance. 22 29 30 This also mimics clinical practice, where emergency physicians are not given this information during clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging physician determination as a criterion is an appropriate measure to test experimental validity in this circumstance, as there is no gold-standard classification to establish appropriateness or has not been experimentally validated. 28 Given validation testing tends to perform better on data used to construct a classification or scale, examining EDAC with a panel of physicians who are unaware of the EDAC’s components can provide a more unbiased estimate of EDAC’s true accuracy and performance. 22 29 30 This also mimics clinical practice, where emergency physicians are not given this information during clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the outbreak of COVID-19, the interRAI organization ( , accessed on 15 December 2021) developed a web-based screening tool to identify vulnerable elderly and adults with disabilities living in the community who were at risk during the pandemic and to determine individuals who required further assessment and/or intervention. InterRAI is a non-profit network of international researchers, clinicians, and policy experts that develops and validates comprehensive assessments to identify the strengths, preferences, and needs of vulnerable persons with complex health conditions [ 18 , 19 , 20 ]. The interviews started around the beginning of June.…”
Section: Methodsmentioning
confidence: 99%
“…The survey contains 27 items, some with sub-items, in a closed-ended multiple-choice format. The CVS was developed by including self-reporting questions that were previously validated through their inclusion in two pre-existing interRAI instruments: (a) the interRAI Contact Assessment (CA) [ 21 ] and (b) the interRAI Check-Up (Self-Reported version) (CU) [ 19 , 22 ]. Both pre-existing tools have been tested and used with vulnerable community-dwelling older adult populations in jurisdictions in Canada and South Africa and found to have a sufficient level of validity and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these data are from the province of Ontario; however, that province still uses an older version of the nursing home instrument 2 ( 75 , 76 ) that excludes self-report items so data from the province of New Brunswick based on the newer interRAI LTCF assessment were used instead. Second, pilot or regional implementations of interRAI systems were done for community mental health services [using interRAI Community Mental Health ( 44 )], wellness checks in home care [using the interRAI Check-Up Self-report version ( 77 , 78 )], and emergency department screening [using the interRAI Emergency Department Contact Assessment ( 79 )] of older adults in acute hospitals. The third type of implementation was research-only use of interRAI self-report items in telephone and on-line surveys of the general population.…”
Section: Methodsmentioning
confidence: 99%
“…The responses are strictly based on the person's self-report without clinical judgement being applied by the interviewer. Previous research has reported in the reliability and validity of the CU-SR in community-based research ( 77 , 78 ).…”
Section: Methodsmentioning
confidence: 99%